2018
DOI: 10.1534/g3.118.200539
|View full text |Cite
|
Sign up to set email alerts
|

A Drosophila CRISPR/Cas9 Toolkit for Conditionally Manipulating Gene Expression in the Prothoracic Gland as a Test Case for Polytene Tissues

Abstract: Targeting gene function with spatial or temporal specificity is a key goal in molecular genetics. CRISPR-Cas9 has greatly facilitated this strategy, but some standard approaches are problematic. For instance, simple tissue-specific or global overexpression of Cas9 can cause significant lethality or developmental delays even in the absence of gRNAs. In particular, we found that Gal4-mediated expression of UAS-Cas9 in the Drosophila prothoracic gland (PG) was not a suitable strategy to disrupt gene expression, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…However, homozygous IRP1A FCF flies were not viable on regular fly media, indicating that the inserted FRT sites had generated a loss-of- IRP1A -function allele. Therefore, we employed a second CRISPR strategy, where we crossed flies that specifically expressed CAS9 in the PG 20 to flies expressing two gRNAs that targeted IRP1A (Supplementary Table 1). The resulting F1 progeny also displayed PG-specific autofluorescence and 100% lethality on regular fly media (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, homozygous IRP1A FCF flies were not viable on regular fly media, indicating that the inserted FRT sites had generated a loss-of- IRP1A -function allele. Therefore, we employed a second CRISPR strategy, where we crossed flies that specifically expressed CAS9 in the PG 20 to flies expressing two gRNAs that targeted IRP1A (Supplementary Table 1). The resulting F1 progeny also displayed PG-specific autofluorescence and 100% lethality on regular fly media (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To generate lines for tissue-specific CRISPR-based deletion of Hph and sima/HIF-1a , double guide RNAs were cloned into plasmid pCFD6 82,83 (Addgene #73915). The Hph construct should lead to the deletion of part of the genomic region encoding the dioxygenase domain common to all Hph isoforms, and the sima gRNAs target the region encoding that protein’s DNA-binding domain.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, CRISPR/Cas9 approaches allow scientists to precisely alter gene function via (i) classic CRISPR to introduce short INDELs, (ii) HR-based CRISPR for homology-based gene replacements or deletions, (iii) somatic CRISPR for conditional gene disruption, (iv) CRISPRi, (i = interference) to interfere with gene transcription, and (v) CRISPRa (a = activation) to upregulate gene activity. Studies have shown that it is possible to conditionally target genes of interest by exerting spatial and temporal control over Cas9 expression or using ligand-activated Cas9 variants [ 8 , 10 , 12 , 13 ]. The rapid advances in CRISPR technologies have made it a popular choice over earlier nuclease-based gene-editing approaches like meganucleases (MNs) [ 14 , 15 ], zinc finger nucleases (ZFNs) [ 16 18 ], and transcription activator-like effector nucleases (TALENs) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%